Influence of Feeding Khejri (Prosopis cineraria) Leaves and Moth Fodder (Phaseolus aconitfolius) Alone or in Combination on Feed Intake, Nutrient Digestibility and Blood Parameters in Camel - Nagpal, A. K.; Abo-Donia, F.M. M. (Indian Journal of Animal Nutrition, 2017)
Twelve healthy Bikaneri dromedary camels (Av. age= 2-3 years; Av. BW= 369Â±7.2 kg) were randomally allotted to 3 groups of 4 animals each using completely randomized design. First group was fed dry chaffed moth (Phaseolus aconitifolius) fodder (MF) and the second group was fed dried khejri (Prosopis cineraria) leaves (KL) as sole feed ad lib. In the third group, both moth fodder and khejri leaves (MF+KL) were offered as free choice. Dry matter intake (kg/100 kg BW or kg/kg W0.75) was similar in camels fed moth fodder and combination of moth fodder and khejri leaves and significantly (P